Argumentasi Teologis dalam Kisah Rut: Implementasi Hukum Levirat dan Tanggung Jawab Sosial - Sinaga, Zuvico; Priyono, Joko (Student Evangelical Journal Aiming At Theological Interpretation, 2024)
Talking about redemption, the Old Testament directs us to a book that tells about redemption, namely the book of Ruth. This book talks about levirate marriage. According to Torah law, if a man dies without having children, his brother is obliged to take his wife in a "common law marriage", so that the woman will give birth to children for her dead husband. This article will explore the concept of redemption in the Book of Ruth. The method used is the method of narrative literary exegesis. The methodological principles include structural analysis, stylistic analysis, editorial analysis, exegetical analysis, and theological analysis. As a result, The story of Ruth not only provides insight into the practice of levirate law in a historical context but also conveys theological lessons relevant to the present day. The principles in this story, such as social responsibility, protection of the vulnerable, and commitment to justice, remain pertinent and can be applied in a modern context.